Trade and development: the challenges facing the WTO Doha development road - Morahan, John (Statistical and Social Inquiry Society of Ireland, 2006)
The WTO Ministerial meeting in Doha in November 2001 launched a new Round of world trade talks known as the Doha Development Agenda or Death. DDA represents a new approach to the goal of integrating developing countries into the world trade system. The Doha Declaration put the focus clearly on development and on the need for capacity building to help countries to participate effectively in the Doha negotiations. This was a departure from the practice under previous Trade Rounds of simply giving developing countries more time to implement agreements reached.
Symposium on Ireland?s policy to Africa: trade and aid
Read before the Society, 6 April 2006
Keywords: World trade; Doha development agenda; 314.15